The Adoption of the “Rain Classroom” Online Learning System among Sophomores in Chengdu, China - Zhang, Derong (Scholar: Human Sciences, 2024)
Purpose: This study aims to examine the second-year students’ behavior intention and use behavior towards Rain Classroom online learning system in Chengdu, China. The major variables are used to develop a conceptual framework which are contains perceived usefulness, self-efficacy, attitude, subjective norms, effort expectancy, behavioral intention, and use behavior. Research design, data, and methodology: The quantitative study applied the questionnaire as a tool to collect the data from 500 students in selected three collages in Chengdu. The data were prior approved for content validity and constructs’ reliability in The Item-Objective Congruence (IOC) and pilot test (n=50) of Cronbach’s Alpha. The sampling techniques used are judgmental, stratified random, and convenience sampling. The data was analyzed through Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). Results: The results show most of hypotheses were supported, excepted the relationship between effort expectancy and use behavior. The support relationships are that perceived usefulness, self-efficacy and subjective norms significantly influence attitude. Additionally, self-efficacy, attitude, subjective norms, and effort expectancy significantly influence behavioral intention. Behavioral intention and use behavior are also significantly related. Conclusions: Rain Classroom can provide online learning to achieve a seamless connection between online and offline learning, which can be endorsed by the successful adoption of students in China.